1981
DOI: 10.1007/bf00423403
|View full text |Cite
|
Sign up to set email alerts
|

Human motor unit activity during the onset of muscle fatigue in submaximal isometric isotonic contraction

Abstract: The onset of fatigue has been studied by relating motor unit activity and surface myoelectric activity during constant force isometric contraction in man. The surface (global) EMG of the biceps brachii was recorded using bipolar electrodes. The global EMGs of the other elbow flexors were also recorded. Motor unit activity was recorded simultaneously at three points of the biceps brachii by using wire electrodes. The time course of the integrated surface EMG showed that fatigue occurred right at the beginning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 23 publications
0
37
1
1
Order By: Relevance
“…The maximal isometric strength (MIF) was measured twice (1 min between the measurements) at an elbow flexion joint of 90°for 4 s. The peak force of each 4 s value was determined, and the mean of the two measurements was used for analysis (MaTon 1981).…”
Section: Isometric Strength and Muscular Fatiguementioning
confidence: 99%
“…The maximal isometric strength (MIF) was measured twice (1 min between the measurements) at an elbow flexion joint of 90°for 4 s. The peak force of each 4 s value was determined, and the mean of the two measurements was used for analysis (MaTon 1981).…”
Section: Isometric Strength and Muscular Fatiguementioning
confidence: 99%
“…The progressive enlargement in its rectified integrated area during submaximal fatiguing contraction is thought to primarily reflect an increase in the number of recruited motor units (MUs) and in their firing rates. 7,10,14 A third possibility is that the size of the motor unit action potential (MUAP) might change during fatiguing contraction. Such possibility indeed has been shown in animal studies, 1,8,18 but has not been systematically investigated in humans.…”
mentioning
confidence: 99%
“…In both these applications muscles contracted dynamically and briefly. There are other studies where decrease in frequency was observed which resulted in fatigue could be explained as central or peripheral in nature [27][28][29] . These observations corroborated with the decrease in the frequency during UH load carriage by Indian soldiers of the present study.…”
Section: Discussionmentioning
confidence: 99%